HYDRAULIC PERFORMANCE AND RELIABILITY ASSESSMENT OF STREET INLET WITH ENHANCEMENT THROUGH PERVIOUS CONCRETE CURB - KAMARUL ZAMAN, `AIFAA BALQIS (2020)
Street inlet is an opening placed on the street functions to discharge stormwater into the underground drainage system. However, the current street inlets practiced in Malaysia often found failed to perform efficiently which cause water ponding and consequently lead to urban flash floods. Henceforth, this research was conducted to assess the hydraulic performance of several typical street inlets by means of experiments. In providing better assessment, the uncertainties associated by the simulated flows during the experiment which is known to be one of the random variables in the design of this structure were also considered, leading to the assessment on the reliability of street inlets through the use of probabilistic approaches. Herein, the hydraulic performance of the three grate and four curb-opening inlets designs implemented in Malaysia were chosen as case studies.